A survey of nurses to assess transfusion practice at the bedside using an electronic identification system: Experience at a university hospital. Issue 1 (4th January 2021) - Nakamura, Yuki; Furuta, Yoshiaki; Tokida, Miho; Ichikawa, Kayoko; Shirahata, Mineko; Uzawa, Kumiko; Takizawa, Makiko; Okubo, Mitsuo; Ohsaka, Akimichi
Abstract: Objectives: The objective of this study was to assess the performance and recognition of transfusion practice at the bedside by nurses in our hospital, where a barcode‐based electronic identification system (EIS) has been used since 2002. Background: More than half of the steps in the transfusion chain are dependent on nurses' awareness and skills. Methods: Our transfusion policy at the bedside includes two‐person checking of the patient and two‐person signing of the label at the time of collecting blood samples for pre‐transfusion testing and two‐person blood administration, which generally involved a doctor–nurse pair but sometimes involved two nurses. Anonymous, paper‐based questionnaires were sent in January 2018 to 1051 nurses who were working in Juntendo University Hospital, Tokyo, Japan. The questionnaire consisted of three parts: (a) background of respondents, (b) performance of collection of blood samples for pre‐transfusion testing and (c) performance of pre‐transfusion check procedures at the bedside using an EIS based on a total of 20 questions. Results: There was a good response rate of individual nurses (1006/1051, 96%). Most nurses (>90%) performed two‐person checking of the patient and two‐person signing of the label at the time of collecting blood samples. Most nurses (>90%) performed two‐person blood administration involving a doctor–nurse pair and electronic pre‐transfusion check using an EIS before blood administration. Conclusions: The survey revealed that most nurses complied with our transfusion policy at the bedside, but some nurses did not. Further education/training and continuous support by the transfusion service may be needed for all nurses.